"They Will Post a Law About Playing Soccer" and Other Ethnic/Racial Microaggressions in Organized Activities Experienced by Mexican-Origin Families. (September 2016) - Lin, Alex R.; Menjívar, Cecilia; Vest Ettekal, Andrea; Simpkins, Sandra D.; Gaskin, Erin R.; Pesch, Annelise
Organized activities have been found to provide positive experiences for Latino adolescents to develop confidence and learn critical life skills; however, these programs are sometimes a context where youth encounter negative experiences related to ethnic/racial microaggressions (ERMs). This qualitative study explores the types of ERMs that Mexican-origin parents and adolescents encountered in their organized activities experience. Parents were mainly concerned about SB-1070 and the associated law enforcement practices that posed a threat to transporting their children to and from the organized activity site. Adolescents reported that they encountered overt (e.g., ethnic teasing) as well as covert forms of discriminatory behavior (e.g., implicit ethnic stereotypes) from peers and adult leaders. Attention to the processes of ERM is critical to helping practitioners promote positive intergroup relations so that more Latinos will participate and stay active in organized activities.